Conceptualising learnings in the coaching process: an effective approach leadership development - Nawab Zadah Khan, Nasreen Khanum; Arshad, Mohd Mursyid; Ismail, Ismi Arif; Omar, Zoharah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Various types of learning approaches play different role and influence towards the leadership development process. This knowledge will allow a coach to understand the learning needs of a coachee which enable them to tailor their approach to maximise the benefits and impact of a coaching process to a coachee. This conceptual paper will discuss on what kind of learning happens within the coaching process and understanding how this learning process helps to improve leadership skills as part of the leadership development programme. Therefore, all metatheories of learnings for human resource development including humanistic, social learning, constructivism as well as behaviourism and cognitivism will never standalone but is usually adapted and blended to fit a particular needs and situation (Swanson & Holton III, 2009). The different learning approaches outlined in this paper are analysed based on the experiences of coachee and coach. Learnings are studied in the context what kind of learning happens within the coaching process and how it contributes in the change in leadership attributes in executive leaders.